Associação entre síndrome de burnout, uso prejudicial de álcool e tabagismo na enfermagem nas UTIs de um hospital universitário - Fernandes, Larissa Santi [UNESP]; Nitsche, Maria José Trevizani [UNESP]; De Godoy, Ilda [UNESP] (FapUNIFESP (SciELO), 2018)
The article aims to determine the presence of burnout syndrome among professionals in the field of Nursing in the Intensive Care Unit in a university hospital and a possible association with consumption of alcohol and tobacco. Participants were 160 nursing professionals from 04 intensive care unit of a university hospital in the period from March 2013 to February 2014. We used a structured questionnaire, plus the smoking history, Maslach Burnout Inventory, Alcohol Use Disorders Identification Test, Fagerström Dependence Questionnaire and the measurement of carbon monoxide. We used Fisher’s chi-square or Fisher exact test. Syndrome was found in 34 professionals, most of them female, married and young adults. 18 professionals reported being smokers. 6,4% of Nursing Assistants, 50% Practical Nurses and Nurses 71,4% drank moderate; 5,4% Nursing Assistant and 14,3% Nurses scored default risk drinking and only 01 Practical Nurses had possible alcohol dependence. There was a positive association of the syndrome with smoking in 01 ICU. Final considerations: Hospital Intensive Care services need assistance from the managers of services for the purpose of caring for the health of their caregivers.
Association between burnout syndrome, harmful use of alcohol and smoking in nursing in the ICU of a university hospital
Keywords: Alcoholism; Burnout; Intensive care nursing; Smoking